Salmonella typhimurium strain SL7207 induces apoptosis and inhibits the growth of HepG2 hepatoma cells in vitro and in vivo - Baowei Li; Hongwei He; Shenghua Zhang; Wuli Zhao; Naren Li; Rongguang Shao (Elsevier, 2012)
Salmonella typhimurium is probably most extensively studied tumor-targeting bacteria and SL7207 is one of its attenuated strains. SL7207 was first made for bacterial vaccine development and its therapeutic efficacy and safety for hepatocellular carcinoma has not been characterized. In this study, the inhibitory ability of SL7207-lux on human hepatoma HepG2 cells was tested in vitro and in vivo. A bacterial luminescent gene cluster (lux CDABE) was transfected into SL7207 to better monitor the invasion of the bacteria. The results show that SL7207-lux can rapidly enter HepG2 cells and localize in the cytoplasm. This invasion represses cell proliferation and induces apoptosis. In vivo real-time invasion studies showed that the bacteria gradually accumulate in the tumor. This enrichment was confirmed by anatomic observation at 5 days after inoculation. About 40% of tumor growth was inhibited by SL7207-lux at 34 days post-treatment without significant loss of body weight. The area of necrosis of tumor tissue was clearly increased in the treated group. Bacterial quantification showed that the number of colony-forming units per gram of bacteria within tumor tissue was approximately 1000-fold higher than that of liver and spleen. These data suggest that attenuated S. typhimurium strain SL7207 has potential for the treatment of cancers.